Contagious policies: An analysis of spatial interactions among countries' capital account policies - Andreas Steiner (Osnabrück University, Institute of Empirical Economic Research, 2010)
Countries' capital account policies might be contagious in the sense that domestic policies are driven by other countries' policies. A model of strategic interactions is developed to show that countries' best response to policy changes elsewhere consists in imitating this policy. Using a spatial econometric model, the hypothesis of policy interactions is tested in a large panel data set. The evidence shows that capital account policies are contemporaneously correlated across countries. Concerning fundamentals, the move to a fixed exchange rate regime and an increase in real world interest rates are correlated with the imposition of capital account restrictions.
Keywords: C23; F21; F3; F42; 330; Capital Controls; Strategic Interaction; Panel Data Analysis